Navigating Nigeria's Health Landscape: Population Growth and Its Health Implications - Ridwan Olamilekan Adesola; Emmanuel Opuni; Ibrahim Idris; Olalekan John Okesanya; Ogechukwu Igwe; Modinat Dasola Abdulazeez; Don Eliseo Lucero-Prisno (SAGE Publishing, 2024)
This comprehensive analysis examines the multifaceted impacts of population growth on public health in Nigeria. Drawing parallels with Omran's epidemiological transition model (that focuses on the intricate means that patterns of health and illness are changing, as well as the relationships that exist between these patterns and the sociological, demographic, and economic factors that influence them) and referencing experiences from Chile and Ceylon. The study highlights a substantial rise in Nigeria's population causing a double burden of infectious and non-communicable diseases, leading to higher morbidity, and mortality rates, increased healthcare costs, decreased productivity, and health inequalities, posing significant challenges to the country's healthcare system. Furthermore, the correlation between low education levels and health outcomes underscores the importance of addressing systemic deficiencies in Nigeria's educational sector. The article emphasizes the urgent need for strategic interventions to mitigate the adverse effects of population growth on health. Recommendations include revitalizing primary healthcare centers, fostering public-private partnerships to enhance healthcare accessibility, leveraging technological advancements like telemedicine, and promoting initiatives to improve nutrition and environmental sustainability. Moreover, prioritizing education on reproductive health and family planning emerges as a crucial strategy to manage population growth sustainably. In conclusion, the article underscores the imperative for collaborative efforts across sectors to navigate Nigeria's evolving health landscape amidst increasing population growth. By implementing targeted policies and interventions, Nigeria can strive toward achieving universal health coverage, enhancing health outcomes, and ultimately raising the standard of living for its populace.